PENGARUH PENDIDIKAN KESEHATAN TENTANG TEKNIK MENYUSUI YANG BENAR TERHADAP PENGETAHUAN DAN KETERAMPILAN IBU HAMIL DI WILAYAH KERJA PUSKESMAS JAILOLO KECAMATAN JAILOLO KABUPATEN HALMAHERA BARAT - Makapuas, Elen (Journal Of Community & Emergency, 2024)
Knowledge and skills of improper breastfeeding lead to lactation failure and have an impact on the fulfillment of the baby’s nutrition. The purpose is to find out the influence of health education about the correct breastfeeding technique on the knowledge and skills of pregnant women in the work area of the Jailolo Health Center, Jailolo District, West Halmahera Regency. This type of research uses pre – experiment with a pre – test and post – test approach without a control group. Sample determination using Non Probability Sampling with purpose sampling method with a total sample of 46 out of a total population of 86. Data analysis uses a statistical test Paired Samples Test with a value of α is 0.05. The results of the paired samples test the p value knowledge of is 0.00 where the sig value < 0.05 which means that Ho is rejected, there is an influence. In the skill of the Paired Samples Test test results, the p value is 0.00 where the sig value < 0.05, which means that Ho is rejected and Ha is accepted or there is an influence. The conclusion is that there is an influence of health education on the correct breastfeeding techniques on the knowledge and skills of pregnant women in the work area of the Jailolo Health Center, Jailolo District, West Halmahera Regency.